Resources in industrial foodservice establishments in Cavite - Zarraga, Lailani Cueno; Perdigon, Grace P. (2002.)
This descriptive study is about the resources in industrial foodservice establishments in Cavite. The locale of the study is in the Cavite Export Processing Zone Authority (CEPZA) located in Rosario, Cavite. The respondents of the survey were composed of 50 foodservice concessionaires, 250 foodservice workers and 250 customers. The study aimed to describe the resources available in industrial food service establishments in CEPZA. Major problems encountered and solution taken in solving the problems as perceived by food concessionaires and the conditions of contract entered into by concessionaires and plant management were likewise determined. The study also attempted to determine the quality of foods and services provided by concessionaires as perceived by customers and its significant relationship to the resources characteristics of foodservice establishments using the correlation method. Interview, observation schedules and questionnaires were the instruments used to gather information about the foodservice establishments. Results of the study showed that majority of the foodservice concessionaires were belonging to 29-48 age range, college graduates with 1-5 years experience in foodservice. majority of the food service establishments served more than 150 customers per meal. Foodservice workers were below 27 years old, female highschool graduates and receiving a monthly income below 3,000.00. Most of the foodservice operators in CEPZA were found to be single proprietors with one year business contract with the company. The average number of foodservice workers were six to ten per establishment. Majority of the concessionaires initially invested about 50,001 to 100,000 for the business. The daily income was P500 to 1000 while the daily expenses was more than 4,001 - 4500. All of the foodservice operations were open six days a week but only half of these operate from 5 a.m. to 7 p.m. The rest had irregular hours of operation. The food production/process and control methods were found to be existing in the foodservice establishments. Machines such as small and institutional type of equipment were used in kitchen and dining areas. Material such as food and non-food supplies were found adequate. Customers were below 27 years of age, female college graduates and were working as production staff of CEPZA. Major problems encountered and solutions taken in solving the problems were identified in several foodservice areas such as menu planning, purchasing, receiving, storing, issuing, preparation and cooking, serving foods and sanitation. Majority of the foodservice space, equipment facilities and utilities were provided by plant management. A great majority of customers perceived that the quality of foods served to them in terms of taste, method of preparation, cleanliness, portion/size preserving, presentation and garnishing and appropriate temperatures was "very good". The quality of services measured in terms of attitudes and foodservice workers, efficiency of service, light and decor, price in relation to atmosphere, location and comfort rooms was also rated "very good". Capital investment appeared negatively correlated with portion/size of food served. Likewise, length of contract was also correlated with music and location. The availability of institutional utensils/ equipment was positively correlated with the taste of food and efficiency of service. The salary of foodservice workers was positively correlated with presentation and garnishing, light and decor and price in relation to atmosphere. Capital was found to have positive correlation with net income and expense. The study recommends that foodservice workers be paid at least minimum age. Concessionaires must organize a cooperative to lobby better concessions and they must also request feedbacks from the customers by the use of evaluation forms. The local government of Cavite may allow rolling stones within the zone so that concessionaires would have greater access particularly to fruits and vegetables at reasonable cost. More in-depth studies about financial aspects of industrial foodservice, space allocations and sanitation and safety must be concluded.
Thesis (M. Food Service Administration)--University of the Philippines Diliman.
Keywords: Food service -- Philippines -- Cavite